2016
DOI: 10.1016/j.vaccine.2015.11.078
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley fever MP-12 vaccine Phase 2 clinical trial: Safety, immunogenicity, and genetic characterization of virus isolates

Abstract: An outbreak or deliberate release of Rift Valley fever (RVF) virus could have serious public health and socioeconomic consequences. A safe RVF vaccine capable of eliciting long-lasting immunity after a single injection is urgently needed. The live attenuated RVF MP-12 vaccine candidate has shown promise in Phase 1 clinical trials; no evidence of reversion to virulence has been identified in numerous animal studies. The objective of this Phase 2 clinical trial was to (a) further examine the safety and immunogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 21 publications
3
58
0
Order By: Relevance
“…The MP-12 vaccine lot has been used for various vaccine safety and efficacy studies using different animal models, including mice, sheep (adult, pregnant ewes, young, and newborn lambs), cattle (adult, lactating cows, pregnant cows, newborn, and young calves), and rhesus macaques [18,2032]. The MP-12 vaccine is an Investigational New Drug to be tested in humans, and its safety and immunogenicity have been tested in clinical trials, including healthy adults [33,34]. In 2013, the MP-12 vaccine was conditionally licensed to Zoetis Inc. for animal vaccination in the U.S. without specific descriptions in the issuance of a conditional license in terms of applied animal species, pregnancy, or age [35], and new vaccine master seed has been generated accordingly by additional amplification of TSI-GSD-223 in MRC-5 cells [27,36].…”
Section: Development Of the Mp-12 Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…The MP-12 vaccine lot has been used for various vaccine safety and efficacy studies using different animal models, including mice, sheep (adult, pregnant ewes, young, and newborn lambs), cattle (adult, lactating cows, pregnant cows, newborn, and young calves), and rhesus macaques [18,2032]. The MP-12 vaccine is an Investigational New Drug to be tested in humans, and its safety and immunogenicity have been tested in clinical trials, including healthy adults [33,34]. In 2013, the MP-12 vaccine was conditionally licensed to Zoetis Inc. for animal vaccination in the U.S. without specific descriptions in the issuance of a conditional license in terms of applied animal species, pregnancy, or age [35], and new vaccine master seed has been generated accordingly by additional amplification of TSI-GSD-223 in MRC-5 cells [27,36].…”
Section: Development Of the Mp-12 Vaccinementioning
confidence: 99%
“…A total of 19 volunteers were vaccinated with the MP-12 vaccine (1×10 5 pfu, i.m.) and 18 (95%) had increased PRNT 80 titers of ≥ 1:20 by 28 dpv, and maintained 1:20 or higher titers for 12 months afterwards [34]. Follow-up evaluation of those volunteers showed that eight of nine tested sera still maintained neutralizing antibodies of ≥ 1:20 at five years post vaccination.…”
Section: Application Of the Mp-12 Vaccine To Human Usementioning
confidence: 99%
See 1 more Smart Citation
“…Phase 2 trials have also been completed for vaccines against Chikungunya and Rift Valley Fever virus, although the Chikungunya vaccines are likely to reach the market faster since their development is being driven by commercial organisations. The RVFV vaccines were tested by the US Army and therefore may not be immediately available for the general population [28]. It is interesting to note that new RVFV vaccines are being developed for animal vaccination but to date there have been no trials of these vaccines in humans [29][30][31].…”
Section: Progress Towards Disease Controlmentioning
confidence: 99%
“…In the United Kingdom, and subsequent to the Ebola outbreak in West Africa, vaccine networks for human and veterinary vaccines have formed to prioritize vaccine efforts in these respective contexts [61], while the Department of Health, together with Innovate UK, has supported R&D of vaccine candidates for the prioritized pathogens [62]. As a result of these global initiatives, a number of candidate vaccines are being developed for emerging bacterial and viral pathogens, examples of which, although by no means exhaustive, are cited here [63][64][65][66][67][68][69][70][71][72][73][74]. WHO reports ongoing global vaccine R&D efforts [75] and also tracks the progress of clinical trials for emerging pathogens [76].…”
Section: Vaccine Requirementsmentioning
confidence: 99%